The effect of microwave radiation on biodiesel production - Muhammad Fikri Afiq, Abdul Mutalib (2010)

(untitled)
Microwave radiation is believed to have effect toward biodiesel production.Because of that reason,the purpose of this research is to investigate the effect of microwave radiation toward enhancing the biodiesel production.During experimental phase,transesterification process is used in order to produce biodiesel and microwave oven is used in order to expose the reaction to the microwave radiation. Using enzyme the biocatalyst,the experimental result shows that microwave radiation do affect the enzymatic reaction. The result showed that longer period of exposure to the microwave yields the fastest conversion glycerides into fatty acid methyl ester.The result also showed that higher power,as long as it did not denature the enzyme,will enhance the conversion of the glycerides.